Software design of intelligent interactive autonomous learning system. Issue 3 (4th April 2020) - She, Xue Wen
Aiming at the problems of poor quality of service, low performance of system cluster and low accuracy of parameter calculation in current software design method of autonomous learning system, a software design method of intelligent interactive autonomous learning system is proposed. Through system architecture design, system module design, system interaction design, system network design and system database design, the overall structure of interactive autonomous learning system software is constructed, and the project parameters and capability parameters are calculated by maximum likelihood method and expert estimation method. According to the user's own ability, personalised test questions and learning content are set for users, and the software design of autonomous learning system is realised. The experimental results show that the proposed method has high quality of service, good cluster performance and high accuracy of parameter calculation.